2017
DOI: 10.1016/j.bbalip.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentenone-containing oxidized phospholipids and their isoprostanes as pro-resolving mediators of inflammation

Abstract: Inflammation represents a powerful innate immune response that defends tissue homeostasis. However, the appropriate termination of inflammatory processes is essential to prevent the development of chronic inflammatory disorders. The resolution of inflammation is actively induced by specialized pro-resolving lipid mediators, which include eicosanoids, resolvins, protectins and maresins. The responsible pro-resolution pathways have emerged as promising targets for anti-inflammatory therapies since they mitigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 118 publications
(191 reference statements)
0
37
0
Order By: Relevance
“…Although we find full-length species to constitute a majority of the OxPL content in lean adipose SVF, it is possible that the lipid content still promotes an antioxidant macrophage polarization. There is precedent that certain full-length OxPL, such as the cyclopentenone containing PECPC, carry strong antioxidant and antiinflammatory activity ( 75 , 76 ). Our data support a scenario where ATM come into contact with mainly antioxidant-promoting OxPL in lean healthy adipose tissue, but with proinflammatory full-length OxPL in obese adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we find full-length species to constitute a majority of the OxPL content in lean adipose SVF, it is possible that the lipid content still promotes an antioxidant macrophage polarization. There is precedent that certain full-length OxPL, such as the cyclopentenone containing PECPC, carry strong antioxidant and antiinflammatory activity ( 75 , 76 ). Our data support a scenario where ATM come into contact with mainly antioxidant-promoting OxPL in lean healthy adipose tissue, but with proinflammatory full-length OxPL in obese adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Watson et al ( 81 ) first described PEIPC, shown to be a proinflammatory mediator ( 23 ) thought to activate the NLRP3 inflammasome in a caspase-11–dependent manner ( 16 ). PECPC, containing a cyclopentenone group and bearing a strong structural resemblance to Prostaglandin J2, has been reported to be an activator of Nrf2 ( 76 , 82 , 83 ). Of the truncated species, the “carbonyl” class denotes the presence of an aldehyde or carboxylic acid on the oxidized moiety, and contains POVPC, PGPC, PONPC, and PAzPC.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike enzymatic oxidation, non-enzymatic oxidation, which occurs during I/R, is not site-specific. Therefore, oxidative stress may result in the production of OxPL with anti-inflammatory properties; however, most OxPLs have potent inflammatory effects [ 34 ]. Cyclopentenone containing OxPLs like 1-palmitoyl-2-epoxyisoprostane-sn-glycero-3-PC (PEIPC) and 15-deoxy-Δ12,14-prostaglandin J2 share similar structures.…”
Section: Discussionmentioning
confidence: 99%
“…This response to OxPAPC has been documented both in vitro and in vivo [5961]. Some cyclopentenone and isoprostaine OxPAPC components, which activate Nrf2, mimic structurally related pro-resolving eicosanoids and exert robust anti-inflammatory activity [62, 63]. OxPAPC is among a limited number of biological molecules that are capable of protecting the integrity of the endothelial barrier in the inflamed lung [64, 65].…”
Section: Protective and Adaptive Effects Of Oxplmentioning
confidence: 99%